Pendampingan Pengemasan Produk Wisata Budaya “Merti Desa” Doplang - Aurilia Triani Aryaningtyas; C Susmono Widagdo; Renny Aprilliyani (Cv. Utility Project Solution, 2022)
Doplang Village has a variety of unique traditions that have great potential to be presented as a tourist spot, one of which is the